1995
DOI: 10.1007/bf02048026
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for extent of lymph node dissection for right colon cancer

Abstract: The dissection procedure for right colon cancer involved removal of 10 cm of normal bowel both proximal and distal to the lesion and, in the central direction, dissection of regional lymph nodes along the main trunk artery up to main nodes, i.e., nodes situated anterior to the surgical trunk, which was confirmed to have a therapeutically satisfactory benefit. Infrapyloric lymph nodes must be dissected when metastasis to the nodes is suspected. In cases of cecal or ascending colon cancer in which the middle col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 5 publications
5
101
1
15
Order By: Relevance
“…This part of the superior mesenteric vessels is by some authors called the "surgical trunk" [14][15][16]. However, the close relationship of the various embryologically defined components of the viscera entails that vascular architecture, especially venous drainage, is complex and variable [14,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…This part of the superior mesenteric vessels is by some authors called the "surgical trunk" [14][15][16]. However, the close relationship of the various embryologically defined components of the viscera entails that vascular architecture, especially venous drainage, is complex and variable [14,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Entsprechend ergibt sich eine distale Resektionsgrenze im Bereich des linken Colon transversum. Da in dieser Tumorlokalisation auch eine lymphogene Metastasierung über das große Netz Richtung Magenantrum und weiter zum Pankreaskopf hin [700] stattfindet, werden neben der Skelettierung der großen Magenkurvatur und Resektion der Gastroepiploica-dextra-Arkade und damit der rechtsseitigen Omentumanteile auch die Lymphknoten über dem Pankreaskopf disseziert.…”
Section: Vorgehen Bei Karzinomen Des Coecums Und Des Colon Ascendensunclassified
“…Left colectomy is therefore increasing in popularity as the uptake of knowledge about feeding vessel increased however variation in practice with regards to the ligation of vascular pedicle root is still remained in controversy. 10,11 Essential point to consider during division of feeding vessel to splenic flexure area is the anatomy network of the blood supply to the splenic flexure as it is variable from person to another. It has studied earlier by Griffith et al, demonstrated anatomical description of colon blood supply in 100 cadavers, revealed that splenic flexure colon supplied by LCA in 89% of cases and 11% by MCA.…”
Section: Resultsmentioning
confidence: 99%